Network Pharmacology and Molecular Docking Approach to Reveal the Underlying Mechanisms of Isorhamnetin in the Treatment of Lymphangitis Carcinomatosis - Harsimran Kaur Hora (International Journal of Bioinformatics and Computational Biology, 2023)
Objective: Lymphangitic carcinomatosis (LC) is a tumor that spreads through lung lymphatics and is most commonly seen secondary to adenocarcinoma. In the majority of cases, LC is a result of tumor cells spreading through the lymphatic system. However, approximately 20% of LC cases can be attributed to lymphangitis caused by tumors obstructing lymphatic drainage. This blockage commonly occurs near the lung hilum, where a centrally located mass can cause inflammation of the lymphatic tubules. Materials and methods: Using, Drugbank and PPI network, stitch identification of the ligands and target proteins was done. Using PyRx the ligands and proteins were docked and to identify the potential ligand, visualization of the docked complexes was done on BIOVIA. ADMET analysis was done for the same ligands to study their pharmacological properties. Results: The proteins AKT1, CYP2C8, and PTK2 were identified as target proteins expressed in LC which docked effectively with the ligand Icaritin respectively. The study's findings indicate that the derivatives of Isorhamnetin such as Icaritin and some others like Quercetin-3'-O-phosphate, and Morin had potential benefits in the prognosis of LC. Conclusion: According to investigation findings, Isorhamnetin itself and Icaritin, Quercetin-3'-O-phosphate, and Morin could be therapeutic for treating LC.
Keywords: AKT1; CYP2C8; Icaritin; Isorhamnetin; Lymphangitis carcinomatosis; Morin; PTK2; Quercetin-3'-O-phosphate